IgG antibodies against phospholipase A2 from Crotalus durissus terrificus: Cross-reaction with venoms from Bothrops species from Argentina - Rodríguez, Juan Pablo (2009)
We examined the ability of IgG anti-crotalic PLA2 to cross-react with Bothrops spp. venoms, from snakes found in the northeast of Argentina. Immunoblotting and ELISA tests showed that IgG anti-crotalic PLA2 recognize antigens of bothropic venoms. Indirect hemolytic activity tests showed that the quantity of antibodies that neutralized 50% of Crotalus durissus terrificus venom (ED50: 2.1 mg IgG anti-crotalic PLA2/100 μg of venom) were also able to neutralize venom from other snakes in the following proportion: 34% of B. alternatus, 18% of B. diporus and 12% of B. jararacussu. Likewise, direct PLA2 activity neutralization tests showed a similar cross-neutralization pattern including 56% of B. alternatus, 29% of B. diporus and 30% of B. jararacussu. In addition, in a myotoxic activity neutralization test, measured by plasma activity of creatine kinase, 35% of B. alternatus venom and 26% of B. diporus venom were neutralized, while no neutralization was detected with B. jararacussu venom. This study presents original data concerning cross-reactions between bothropic venoms from Argentina and IgG anti-crotalic PLA2. Our results suggest that anti-crotalic PLA2 antibodies should not be used to neutralize PLA2 activity of B. alternatus, B. diporus and especially B. jararacussu venoms; nor to enrich commercial antivenoms against these Bothrops species.